2009
DOI: 10.1007/s10620-009-1040-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Motility in Hand-Sewn End-to-End Anastomosis and Functional End-to-End Anastomosis: An Experimental Study in Conscious Dogs

Abstract: In the present study, there are no significant differences between the EE and FEE with regard to the time of the appearance and the rate of propagation of IMC. These results suggest that the effect of functional end-to-end anastomosis on postoperative motility is not different from that of hand-sewn end-to-end anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Although delayed aboral transit of ingesta across side-to-side anastomoses (compared with that through end-to-end anastomoses) has been reported, it has been shown that intestinal motility in either conformation is not significantly different from that of healthy dogs that have not undergone intestinal surgery. 34,35 Trichobezoar obstruction at a circular end-to-end stapled anastomosis site has been reported and was presumed to result from entanglement with the exposed regions of staples in the intestinal lumen. 36 These reports, along with the occurrence of impactions at some of the previously stapled anastomosis sites for dogs in our study that required additional surgery, may indicate the need for development of absorbable staple materials to decrease the risk of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Although delayed aboral transit of ingesta across side-to-side anastomoses (compared with that through end-to-end anastomoses) has been reported, it has been shown that intestinal motility in either conformation is not significantly different from that of healthy dogs that have not undergone intestinal surgery. 34,35 Trichobezoar obstruction at a circular end-to-end stapled anastomosis site has been reported and was presumed to result from entanglement with the exposed regions of staples in the intestinal lumen. 36 These reports, along with the occurrence of impactions at some of the previously stapled anastomosis sites for dogs in our study that required additional surgery, may indicate the need for development of absorbable staple materials to decrease the risk of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]6,9,11,12 Only two cases reported that the dogs were hospitalised for 2 days postoperatively, 3,9 while the rest lacked related information. 2,4,6,11,12 In our case, 4 days of hospitalization were initially suggested to minimize the risk of small intestine dehiscence which is higher on the third day 25 and to monitor the dog until completion of the lag phase of intestinal healing, 25 but the owner decided to take his dog home one day earlier, due to financial restraints.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, the term “functional end-to-end anastomosis” [ 5 ] was used both in ASSA and Kono-S anastomosis [ 21 ]. As a matter of fact, ASSA is not “end-to-end” but “side-to-side” in configuration, and experimental studies [ 22 23 24 ] have also proved ASSA was less functional than end-to-end anastomosis regarding intestinal motility and bacterial growth. From this viewpoint, Kono-S anastomosis might better deserve the naming of “functional end-to-end anastomosis.” Secondly, intervening mesentery in both ISSA and Kono-S can be divided close to the bowel, resulting in better preservation of vascularization and innervation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%